Development and Experimental Characterization of a Small Scale Solar Powered Organic Rankine Cycle (ORC). (November 2016) - Taccani, Rodolfo; Obi, John Besong; De Lucia, Maurizio; Micheli, Diego; Toniato, Giuseppe
Abstract: Solar thermal power plants have been widely studied in recent years as solar energy is clean, affordable and largely available. The possibility of converting solar thermal energy into electricity with small scale (lower than 10 kWe) Organic Rankine Cycle (ORC) plants operating at low temperature (lower than 130 °C), seems today a viable option. In this paper, the design and development of a prototypal small scale ORC plant (< 10 kWe) is presented. The ORC, equipped with a scroll expander and installed in Florence, Italy, is powered by parabolic trough solar collectors (PTC) with collector surface area of 100 m 2 . In the first part of the paper the experimental data collected during the lab tests are presented. Then, the data collected during the field test are presented and discussed. A gross electrical efficiency up to 8% has been achieved. The value of net efficiency is dependent on the power absorbed by the auxiliary components that have not been optimized yet.